أثر مهارات التواصل الزواجي على أنماط التنشئة الاجتماعية للأبناء لدى المتزوجين العمانيين المتغير المعدل: سنوات الزواج = The impact of marital communication skills on socialization patterns of children among Omani spouses: The moderator role years of marriage - Al-Habsi, Ali Abdullah Mohammed; Abdul Rashid, Khadijah Khalilah (المؤسسة العربية للتربية والعلوم والآداب = The Arab Institution for Education, Science and Arts (AIESA), 2023)
هدفت هذه الدراسة للكشف عن أثر مهارات التواصل الزواجي على أنماط التنشئة الاجتماعية للأبناء لدى الأزواج العمانيين المتغير المعدل سنوات الزواج ، اعتمد الباحث المنهج الكمي الوصفي، حيث قام بتطبيق مقياس لمهارات التواصل الزواجي وأنماط التنشئة الاجتماعية للأبناء على عينة عشوائية مكونة من ٤٠٠ من الأزواج العمانيين وتتمثل متغيرات الدراسة في مهارات التواصل الزواجي كمتغير مستقل ويتكون من خمسة أبعاد هي (مهارة القدرة على الحوار، مهارة القدرة على الإصغاء، مهارة القدرة على الفهم مهارة حل المشكلات الزوجية، مهارة التعبير العاطفي)، وأنماط التنشئة الاجتماعية كمتغير تابع ويتكون من عشرة أبعاد هي نمط تقبل الأبناء، نمط التعاون بين أفراد الأسرة، نمط مراعاة ميول الابناء نمط التحاور مع الأبناء، نمط تحمل الابناء للمسئولية، نمط العناية بالأبناء، نمط المساواة بين الأبناء، نمط الحماية للأبناء، نمط الثبات في معاملة الأبناء، نمط الاعتدال في معاملة الأبناء)، وقد اسفرت النتائج عن وجود درجة ممارسة عالية لمهارات التواصل الزواجي وأنماط التنشئة الاجتماعية لدى الأزواج العمانيين، كما كشفت النتائج عن تحقيق النموذج البنائي لمتغيرات الدراسة لمؤشرات حسن المطابقة، وتمتع النموذج بالثبات والصدق، كما أظهرت النتائج وجود تأثير إيجابي متوسط ومباشر دال إحصائيا لمهارات التواصل الزواجي على أنماط التنشئة الاجتماعية للأبناء لدى الأزواج العمانيين، كما كشفت النتائج أن مهارة الإصغاء إلى شريك الحياة) الأكثر تأثيرا على أنماط التنشئة الاجتماعية للأبناء في حين أن مهارة التعبير العاطفي) هي الأقل تأثيرا على أنماط التنشئة الاجتماعية للأبناء، كما كشفت النتائج أنه ليس هناك تأثير للمتغير المعدل (سنوات الزواج) على العلاقة بين مهارات التواصل الزواجي وأنماط التنشئة الاجتماعية للأبناء لدى الأزواج العمانيين، وقد توصلت الدراسة إلى مجموعة من التوصيات = This study aimed to reveal the impact of marital communication skills on socialization patterns of children among Omani spouses: The moderator role years of marriage. The researcher adopted the descriptive quantitative approach, where he applied a scale of marital communication skills and patterns of socialization of children on a random sample of 400 Omani spouses. The variables of the study are marital communication skills as an independent variable and socialization patterns of children as a dependent variable. The marital communication skills scale consists of five dimensions: the ability to listen, the understanding skill, the solving marital problems skill, the emotional expression skill. The socialization patterns consists of ten dimensions: Pattern of parental acceptance, Parental Patterns of Cooperation in Parent–Child Interaction, pattern of children tendencies, pattern of children dialogue, pattern of children responsibility, pattern of children caring, pattern of equality between children, pattern of children protection, pattern of stability in the children treatment, pattern of moderation in the children treatment. The results revealed a high levels of marital communication skills and children’s socialization patterns among Omani spouses. The results also revealed that the structural model of the study variables achieved good matching indicators. The results also showed a positive, medium and direct impact of marital communication skills on children’s socialization patterns. The results revealed that the skill (listening to the life partner) is the most influential on the children’s socialization patterns, while the skill (emotional expression) has least impact. The results also presented that it is no impact of the moderator variable (years of marriage) on the relationship between marital communication skills and the children’s socialization patterns among Omani spouses. Several recommendations were presented on the basis of the finding.